Effects of Aerobic Exercise, Cognitive and Combined Training on Cognition in Physically Inactive Healthy Late-Middle-Aged Adults: The Projecte Moviment Randomized Controlled Trial - Roig-Coll, Francesca; Castells-Sánchez, Alba; Lamonja-Vicente, Noemí; Torán-Monserrat, Pere; Pera, Guillem; García-Molina, Alberto; Tormos, José Maria; Montero-Alía, Pilar; Alzamora, Maria Teresa; Dacosta-Aguayo, Rosalía; Soriano-Raya, Juan José; Cáceres, Cynthia; et al. (Frontiers in Aging Neuroscience, 2020)
Background: Lifestyle interventions are promising strategies to promote cognitive health in aging. Projecte Moviment examines if aerobic exercise (AE), computerized cognitive training (CCT) and their combination (COMB) improves cognition, psychological health and physical status compared to a control group. We assessed the moderating role of age and sex and the mediating effects of cardiorespiratory fitness (CRF), physical activity (PA) and psychological health on intervention-related cognitive benefits. Methods: This was a 12-week multi-domain, single-blind, proof-of-concept randomized controlled trial. 96 healthy adults aged 50 to 70 years were assigned to AE, CCT, COMB and a wait-list control group. The per protocol sample, which completed the intervention with a level of adherence >80%, consisted of 82 participants (62% female; age = 58.38 ± 5.47).We assessed cognition, psychological health, CRF and energy expenditure in PA at baseline and after the intervention. We regressed change in each outcome on the treatment variables, baseline score, sex, age and education. We used PROCESS Macro to perform the mediation and moderation analyses. Results: AE benefited Working Memory (SMD=.29, p.037) and Attention (SMD=.33, p.028) including the Attention-Speed (SMD=.31, p.042) domain, compared to Control. COMB improved Attention (SMD=.30, p.043), Speed (SMD=.30, p.044) and the Attention-Speed (SMD=.30, p.041) domain. CTT group did not show any cognitive change compared to Control. Sportive PA and CRF increased in AE and COMB. Age and sex did not moderate intervention-related cognitive benefits. Change in sportive PA, but not in CRF, significantly mediated improvements on Attention-Speed in AE. Conclusion: A 12-weeks AE program improved Executive Function and Attention-Speed in healthy late-middle-aged adults. Combining it with CCT did not provide further benefits. Our results add support to the clinical relevance of even short-term AE as an intervention to enhance cognition and highlight the mediating role of change in sportive PA in these benefits. Clinical Trial registration: ClinicalTrials.gov. Identifier: NCT03123900.